A persecução penal dos crimes praticados na internet: o cibersexo com crianças e adolescentes - Dias, Thiago José Garreta Prats (2020)
The present paper aims to conduct a theoretical study on the impacts of the internet, which it identifies as one of the greatest aspects of modernity and globalization, especially regarding the criminal prosecution of crimes committed in the virtual environment against children and adolescents, with a focus on exchange of messages with erotic and sensual content, known as sexting, addressing legal reflexes, lawsuits and penalties, such as new investigation techniques, mechanisms of persecution and classification of related crimes